SUSTAINABLE AND RESPONSIBLE INVESTMENT (SRI) FROM YEAR 2000 TO 2021: A BIBLIOMETRIC ANALYSIS - Mohamad Hanif Abu Hassan; Purnomo M Antara; Muhammad Zarunnaim Haji Wahab (Journal of Islamic, Social, Economics and Development, 2022)
With the growth of SRI issuances, there are various studies that have been conducted in this area. Thus, this study aims to present the current trend of the study on SRI by adopted a bibliometric analysis based on Scopus database. Based on the keywords used on the title and abstract of the article, the study manages to obtain 668 documents for further analysis. Various tools have been employed, such as Microsoft Excel to conduct the frequency analysis, VOS viewer for data visualization, and Harzing’s Publish or Perish for citation metrics and analysis. This study reports the results using bibliometric indicators such as document type, source type, publication year and its trends, languages, subject area, keywords analysis and citation analysis. Based on the findings, there is a tremendous growth of publications on SRI’s studies over the years since 2000 until 2021. The results also indicate that the topic on SRI is started becoming an emerging topic since 2000 and boosted dramatically in 2005 until today. Thus, its proven that the SRI is the new research area that not well covered until today. Relatively, the SRI is a new instrument that has strong demand and good potential for growth in the future in line with the increasing of the awareness among many parties around the world. This study has provided some major implications. On behalf of regulatory bodies (policy makers), they can use the outcome of this study as a reference in their future guidelines by utilising the data and information on the current situation in SRI industry. On behalf of academicians, the research provides an opportunity to explore a new research area related to product innovation, which is the SRI’s concept as well as will add to the current and existing academic literature that is still poorly documented up to date.